THE ROLE OF MEDIA IN DIRECTING YOUTH TO VOTE IN THE KURDISTAN REGIONAL PARLIAMENT ELECTIONS 2013,DUHOK CITY AS A MODEL - Abdullah, Zeravan Ameen; Urood, Kandeez (Journal of Duhok University, 2018)
This academic study comes as a result to answer many questions that concerns many people. To shed lights on the most usable media tools among youth (aged 18-35) in Dohuk city. To obtain information about the Parliament election of Kurdistan Region of 2013 as a right for people to get sufficient information from sources. As a right of citizens to obtain knowledge as a protection of using multimedia tools, as right of expression in using different tools to express themselves, the publication, the advertisement, the publication and these are the fundamental protected rights in the constitution. The study focused on these points, and broad humanitarian, geographical and subjective issues. The study found that the Kurdish Media used intestinally or unintentionally the indirect violence (cultural) against members of the society. And the study also found the existence of professional confusion in the media despite having great humanitarian, financial capacities.